Week 02 : Method of C haracteristics From now on we will study one by one classical techniques of obtaining solution formulas for

PDEs. The first one is the method of characteristics, which is particularly useful when solving first order equations. 1 . C lassification of first-order equations. The general form of first-order PDE ( in R2 ) : F( x , y , u , ux , u y) = 0 , or in R3 : ( x , y ) ∈ D ⊂ R2 . (1) ( 2) ( 3) ( 4)

F( x , y , z , u , ux , u y , uz ) = 0 . Often the following notation is used in 2D: p = ux , q = u y thus the equation can be written as F ( x , y , u , p, q ) = 0 . The linear equations can be classificed into the following cases, from easier to more difficult: 1 . Linear: 2. Semi-linear: 3. Quasi-linear: 4. General case. F ( x , y , u , u x , u y ) = a ( x , y ) u x + b ( x , y ) u y + c( x , y ) u − d( x , y ) . F ( x , y , u , u x , u y ) = a ( x , y ) u x + b ( x , y ) u y − c( x , y , u ) . F ( x , y , u , u x , u y ) = a ( x , y , u ) u x + b ( x , y , u ) u y − c( x , y , u ) .

( 5) ( 6) ( 7)

2. Method of characteristics. We try to find a method to solve the general first-order quasi-linear equation a ( x , y , u ) u x + b ( x , y , u ) u y = c( x , y , u ) . ( 8)

Let’ s start by thinking geometrically. Consider the 3 dimensional space with coordinates ( x , y , u ) . Assume that u = u ( x , y ) is a solution to the equation, it is clear that it represents a surface in the ( x , y, u ) space. Now we explore the geometrical meaning of the equation. Observe that the equation can be written in the form of an inner product         a( x , y , u) a( x , y , u) ux ux  b ( x , y , u )  ⊥ u y  .  b( x , y , u)  ·  u y  = 0 ( 9) c( x , y , u ) −1 c( x , y , u ) −1
 

Therefore all we need to do is to understand the relation between the vector First introduce a new function Ψ : R
3
¡

 

R through

 ux uy  − 1

and the solution. ( 1 0)

Φ ( x , y , u) = u − u( x , y) .

Note that in the RHS of the above, the first u is a variable, the second u is a function. For example, suppose u ( x , y ) = x 2 + y 2 , then the corresponding Φ ( x , y, u ) = u − x 2 + y 2 . Now we easily see that     Φx ux  uy  = −  Φ y  = − ∇Φ . (11) Φu −1

Equations with constant coefficients.   a  b  c On the other hand. 1 . where a . u ) u x + b ( x . And each F gives a solution to the original equation. any surface “woven” by such integral curves is a solution surface. u)  c( x . the main technique in getting φ and ψ is a c = b d   a±c a c = = . The above understanding leads to the following “method of characteristics” due to Lagrange. Solving linear first-order equations. Y . Remark 4. a ( x . Example 5. y ) . quasi. We start with the simplest case. b . we will show how to apply this method. φ . u ) . c   Now we summarize. ψ) = 0 . ∇ Φ ( and also − ∇ Φ ) is a normal vector of the surface Φ = 0 . ψ are obtained through solving the characteristic equations. ( 1 6) where F is an arb itrary function of φ ( x . u ) and ψ ( x . y . 8. As a consequence. y . y . 3. b are constant . from the equation we know that a  b  c is perpendicular to the vector   must be tangent to the surface u = u ( x . u ) u y = c( x . Theorem 1 . As we will see. y . Conversely.linear PDE a ( x . y ) . As a consequence is perpendicular to the solution surface u = u ( x . U ) ( 1 3) ds dU = c( X . 3( b) ) Find the general solution of the equation a u x + b u y = 0. y . The curves mentioned above are called the families of characteristic curves of the equation. b±d b d ( 1 8) In the following. u)  b( x . As we will see soon. The general solution of a first.Recall   ux  uy  − 1 means that geometrically. a b c ( 1 7) ( 1 5) Remark 2. Solution. and any intersection of the level sets of φ and ψ is a solution of the characteristic equations dx d y du = = . c and d are just constants. U ) ( 1 4) ds must be contained in one of the solution surfaces. We start from the simplest case. y ) . y . y . u)   ux uy  − 1 which that the vector curve a of  b  . Remark 3. ( § 2. u ) satisfies F( φ .order. 3. b 0 a ( 20) a . Y . The characteristic equations are dx d y du = = . ( 1 9) . U ) ( 1 2) ds dY = b( X . y. any integral satisfying dX = a( X . Y . We   have shown that the equation is equivalent to the geometrical requirement that is any  X( s)  Y( s)  U( s) is tangent to the solution surface u = u ( x .

ψ = ea − 1 cx u − c− 1 d ( 31 ) ( 32) ( 33) F( φ . one may be tempted to conclude d u − C e− a −1 − 1 cx =0 ( 34) and try to use u − C e − a c x as ψ . u ) and ψ ( x . This means for an arbitrary function f . 8. a b d− cu We have dx d y = d( b x − a y ) = 0 . ( C auchy problem. notice that thus we can take d( a y − b x ) = a d y − b d x = 0 . d are not 0 ? The method still works. 2 2x−3y . This is obviously wrong as d somehow disappeared. d ψ = 0 along the characteristics. solve 3 ux + 2 u y = 0. In the above. ψ) = 0 u = c− 1 d + e − a − 1 cx f ( b x − a y) . Remark 8. Now substituting this into the initial condition. Some times people use the following “method of characteristics”: . F( a y − b x . ( c. d 0 ) What happens when the c. 5( a) ) Oftentimes. u) = 0 u = f ( a y − b x) . we obtain f ( 2 x ) = sin x   ( 26) Therefore x f ( x ) = sin . For example. ( 25) Solution.What we need are two functions φ ( x . 0) = sin x. the value of the solution along some specific curve in the plane is prescribed. Obviously we can take φ = u . We write the characteristic equations dx d y du = = . ( 21 ) ( 22) ( 23) ( 24) As a consequence. § 2. u ) such that d φ = 0 . y ) = sin   As a consequence and gives Example 7. 2 ( 27) u ( x . Example 6. For ψ . From the above example we know that the general solution takes the form u = f ( 2 x − 3 y) . ψ = a y − b x. u ( x . a b −1 −1 dx du du = = a− 1 d − a− 1 c u u = C e − a c x + c− 1 d d e a c x u − c− 1 d = 0 a d− cu dx         down ( 28) ( 29) ( 30) φ = b x − a y. y . It is their values that are arbitrary constants. y . Example 9. the solution satisfies for any function F . One should keep in mind that neither φ or ψ can involve arbitrary constants.

5( c) ) Find the solution of the following Cauchy problem: x ux + y u y = 2 x y . One may wonder. The characteristic equations consists of three equations. with u = 2 on y = x 2 . If you can find general solutions. 8. Pick any two of them. u − log y ) = 0 u = log y + f ( x y ) . ( 47) Solution. y and obtain the solution. 8. F ( x y . t ) . ( 37) dx d y du = = . We need to first find the general solution. −x y 1 dy dx = y −x y dx + x d y = 0   ( 38) ( 39) d( x y ) = 0 . But this fails when any coefficient involves all other variables. ( § 2. Example 1 1 . how to find out φ and ψ efficiently? Unfortunately there may not be any short-cut. On the other hand. ( § 2. 2.First solve then solve dx = a. Example 1 2. 3( h) ) Find the general solution of Solution. then using the value on y = x 2 to determine the arbitrary function involved. The characteristic equations are Using we obtain Thus φ = x y. Anyone who does not believe this should try using this method to the following examples with non-constant coefficients. t by x . from we obtain d u = d log y   y u y − x ux = 1 . This is equivalent to our method but considerably more complicated to use. Equations with non-constant coefficients. 3. x y 2xy dx d y = y x ( 48) ( 49) . Remark 1 0. As a consequence we can take Putting these together we obtain which gives ψ = u − log y. − Find the general solution The characteristic equations are Using dx d y du = = . One way to systematically find φ and ψ is the following. then you have φ and ψ . Finally represent s . ds dy =b ds ( 35) ( 36) us + c u = d to obtain the solution u in the form u = u ( s . ( 40) ( 41 ) ( 42) ( 43) ( 44) ( 45) ( 46) d y du = 1 y d( u − log y ) = 0 .

Example 1 3. 8. F x2 + y2 . ( 61 ) Thus we take Now gives ψ = y ( u − y) . 5( g) ) Solve x ux + y u y = u + 1 Solution. y) = x y + 2 − 4. We have u = 2 along y = x 2 . x ( 53) d u = 2 x d y = 2 y d x = x d y + y d x = d( x y )   ψ = u − x y. x d( u − x y ) = 0 ( 50) ( 51 ) ( 52) y . 8. u− xy =0 x   u=xy+ f Determine the solution. ( § 2. Using the formula for the general solution. The characteristic equations are ( 58) ( 59) ( 60) From we have On the other hand. d( u − y ) u− y =− y dy du u =− +2 dy y     d( ( u − y ) y ) = 0 . x2 = 2. . Solving semi-linear first-order equations.we obtain d On the other hand. dy du dx = = . 3( g) ) Find the general solution of the following equation: y2 ux − x y u y = x ( u − 2 y) . ( 62) ( 63) ( 64) Example 1 4. y x 3 ( 55) ( 56) u( x . ( § 2. we have therefore The general solution satisfies F − y =0 x   can take φ = y . y ) = x 2 on y = x 2 . − x y x ( u − 2 y) y2 dy dx = y2 − xy d x2 + y2 = 0   ( 57) Solution. ( 65) . y ( u − y) = 0 u = y + y− 1 f x2 + y2 . The characteritic equations are dx d y du = = x y u+1 ( 66) with u ( x . that is u x . we have x3 + f ( x) = 2   ( 54) As a consequence f ( x) = 2 − x3. y . we have dy du = − x y x ( u − 2 y)   φ = x2 + y2 .

x x f ( x) − 1 = u x . φ = x2 + ( y + u) 2 . y x− y y+u d( y + u ) dx = y+u x   ( 72) Solution. ( 79) Solution. dy du dx = = . y ( 71 ) u=xf y − 1. Remark 1 6. u2 − ( x − y) 2 = 0 . The characteristic equations are ( 73) ( 74) ( 75) From this we have Thus we can take On the other hand. Note that. Example 1 5. x ψ= u+1 .which easily lead to φ= Thus Now the Cauchy data implies thus As a consequence u( x . the solution is given by F x 2 − ( y + u) 2 . x ( 67) ( 68) ( 69) ( 70) x2 − 1. 3( f) ) Find the general solution of ( y + u ) u x + y u y = x − y. 8. y y +x x x −1 − 1 = y+ 5. − u u2 + ( x + y) 2 u dx dy = u −u   ( 80) ( 81 ) ( 82) d( x + y ) = 0     φ = x + y. d( x − y ) du = x− y u   d u2 − ( x − y) 2 = 0. dy du = − u u2 + φ2 ψ = e2 y u2 + φ2 . The characteristic equation are We have Then we have dy du dx = = . . 5( h) ) solve u ux − u u y = u2 + ( x + y) 2 with u = 1 on y = 0 . ( § 2. in the above we can also use d y d( x + u ) = x+u y   ( 77) d x+u y = const . Solving quasi-linear first-order equations. y) = x y . ( 76) As a consequence. Example 1 7. we have d x2 − ( y + u) 2 = 0 . ( 78) Thus the formula may not be unique. 8. ( § 2. x2 = x2 f ( x) = x + x − 1 .

we observe dx dy = yz − xz   ( 87) Solution. 8( d) ) Solve the following equation y z ux − x z u y + x y x2 + y2 uz = 0 . . Equations with more than two variables. ( 90) Therefore the solutions are obtained by setting F u . 8. 1 + φ2 ≡ 0. x2 + y2 . F( φ . The characteristic equations are ( 88) ( 89) The last invariant can be obtained through dy dz = − xz xyφ   dx dy = y −x   d x2 + y2 = 0   ψ = x2 + y2 . 1 ( 93) =0 ( 92) dy dz = − z yφ   d z 2 + y2 φ = 0   η = z 2 + y 2 φ. The method of characteristics can be applied to higher dimensional problems with no difficulty in principle – it indeed becomes more difficult in practice! Example 1 8.Now from the Cauchy data we have Therefore effectively F has to be and the solution satisfies which leads to F φ . For the second invariant. let’ s denote them by φ . K eep in mind that this f will be determined once some C auchy data is given. z 2 + y2 x2 + y2 for arbitrary f. Clearly one can take φ = u. ψ and η . ( 91 ) 1 . ( 86) e − 2 y − ( x + y) 2 1 /2 6. dy dz du dx = = = . ( § 2. 0 y z − x z x y ( x2 + y2 ) This time we need three invariants. z 2 + y2 x2 + y2 which gives u = f x 2 + y2 . ψ ) = ψ − φ2 + 1 e2 y u2 + ( x + y) 2 − 1 + ( x + y) 2 = 0 u= ± 1 + ( x + y) 2 ( 83) ( 84) ( 85) .

Sign up to vote on this title
UsefulNot useful

Master Your Semester with Scribd & The New York Times

Special offer for students: Only $4.99/month.

Master Your Semester with a Special Offer from Scribd & The New York Times

Cancel anytime.